#foodporn: examining Instagram food influencers through the systems model of creativity. Issue 4 (2nd October 2022) - Drew, Zoe; Fulton, Janet; McIntyre, Phillip
ABSTRACT: Social media influencers (SMIs) are having a profound impact on how diners seek information about culinary establishments and are redefining how the marketing industry promotes restaurants and brands. Although research has confirmed the value of an SMI's electronic word of mouth (eWOM) endorsement on brand recognition and purchase intention, there is limited understanding of the creative practice of these individuals. To address this gap, this research examines Instagram food influencers in Australia, using the systems model of creativity to frame the research. This research found that as an individual agent in a system, Instagram food influencers are impacted by their personal experiences, their immersion in cultural domains, their understanding of the field's preferences and engagement with its social system when creating content. These findings indicate that the systems model of creativity is a sound framework to understand the creative practice of SMIs.